Diminished Pneumococcal-Specific CD4+ T-Cell Response is Associated With Increased Regulatory T Cells at Older Age - He, Samantha W. J.; van de Garde, Martijn D. B.; Pieren, Daan K. J.; Poelen, Martien C. M.; Voß, Franziska; Abdullah, Mohammed R.; Hammerschmidt, Sven; van Els, Cécile A. C. M. (Frontiers in Aging, 2021)
Respiratory infection caused by Streptococcus pneumoniae is a leading cause of morbidity and mortality in older adults. Acquired CD4+ T cell mechanism are essential for the protection against colonization and subsequent development of infections by S. pneumoniae. In this study, we hypothesized that age-related changes within the CD4+ T-cell population compromise CD4+ T-cell specific responses to S. pneumoniae, thereby contributing to increased susceptibility at older age. To this end, we interrogated the CD4+ T-cell response against the immunogenic pneumococcal protein AliB, part of the unique oligopeptide ABC transporter system responsible for the uptake of nutrients for the bacterium and crucial for the development of pneumococcal meningitis, in healthy young and older adults. Specifically, proliferation of CD4+ T cells as well as concomitant cytokine profiles and phenotypic markers implied in immunosenescence were studied. Older adults showed decreased AliB-induced CD4+ T-cell proliferation that is associated with an increased frequency of regulatory T cells and lower levels of active CD25+CD127+CTLA-4-TIGIT-CD4+T cells. Additionally, levels of pro-inflammatory cytokines IFNy and IL-17F were decreased at older age. Our findings indicate that key features of a pneumococcal-specific CD4+ T-cell immune response are altered at older age, which may contribute to enhanced susceptibility for pneumococcal infections.